Exploring the Impact of School Climate on Education: Findings from Recent Research - Bahijah, Ijah; Budiana, Erick; Hakim, Lutpiyah (Rayah Al-Islam, 2024)
تهدف هذه الدراسة إلى استكشاف تأثير المناخ المدرسي على النتائج التعليمية ، بناء على نتائج أحدث الأبحاث. يشمل المناخ المدرسي عناصر مثل السلامة والعلاقات وممارسات التدريس والتعلم والبيئة العامة التي تشكل بشكل جماعي تجربة الطلاب والمعلمين والإداريين. يستخدم هذا البحث طريقة مراجعة الأدبيات المنهجية (SLR) باتباع بيان PRISMA (عناصر الإبلاغ المفضلة للمراجعات المنهجية وطريقة التحليلات التلوية). تستخدم لاستخراج المقالات من قاعدة بيانات النشر أو الهلاك. تسلط الدراسة الضوء على أن المناخ المدرسي الإيجابي يحسن بشكل كبير من الأداء الأكاديمي للطلاب ، والتطور الاجتماعي والعاطفي ، والمشاركة في الأنشطة المدرسية. بالإضافة إلى ذلك ، فإن المناخ المدرسي الإيجابي له أيضا تأثير إيجابي على الرضا الوظيفي للمعلمين ، والنمو المهني ، وفعالية التدريس ، فضلا عن فعالية القيادة ورفاهية مديري المدارس. من خلال تجميع البيانات من الدراسات المختلفة ، تؤكد هذه الدراسة على الدور الحاسم في تعزيز مناخ مدرسي داعم وشامل لتعزيز النجاح التعليمي والرفاهية لجميع أعضاء المجتمع المدرسي This study aimed to explore the impact of school climate on educational outcomes, based on findings from recent research. School climate encompasses elements such as safety, relationships, teaching and learning practices, and the environment as a whole that collectively shape the experiences of students, teachers, and administrators. This research uses the Systematic Literature Review (SLR) method by following the flow of PRISMA statements (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Used to extract articles from the Publish or Perish database. The research highlights that a positive school climate significantly improves students' academic performance, social and emotional development, and engagement in school activities. In addition, a positive school climate also has a positive impact on teacher job satisfaction, professional growth, and teaching effectiveness, as well as leadership effectiveness and principal well-being. By synthesizing data from a range of studies, the study emphasizes the critical role of fostering a supportive and inclusive school climate to promote educational success and well-being for all members of the school community.